RESPONDING TO THE DIGITAL ERA WITH SOCIAL TRANSFORMATION THROUGH TAFSIR AL-QUR'AN FOR GENERATION Z - Erizal Candra Efendi; Usril Rambe; Sobhan Sobhan (Adisam Publisher, 2025)
This study aims to analyze the relevance of the interpretation of the Qur'an as a socio-moral guide for Generation Z in the digital era. Generation Z, who grew up in a dynamic technological and social media environment, faces various moral and social challenges such as the spread of hoaxes, cyberbullying, and the tendency to pursue popularity that often conflicts with religious values. Through a qualitative approach with the library research method, this study identifies relevant interpretations of the Qur'an in addressing these problems. The results of the study indicate that the interpretation of the Qur'an that emphasizes communication ethics, information verification, social responsibility, and universal moral values is very relevant to answering the challenges faced by Generation Z in the digital era. The contextual interpretation approach is able to connect the teachings of the Qur'an with modern social realities, providing practical, applicable guidance for dealing with cyberspace. In addition, this study proposes the need to adjust the Islamic religious education curriculum to be more responsive to developments in technology and social media, so that it can form a more ethical, critical, and responsible Generation Z. This study concludes that the interpretation of the Qur'an not only functions as an explanation of religious texts, but also as a tool to form a solid moral character, strengthen Muslim identity, and help Generation Z face digital challenges wisely. These findings contribute to the development of religious education that is relevant to the needs of the times and becomes a guide for educators, parents, and education practitioners in guiding Generation Z.